2019
DOI: 10.3855/jidc.10926
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of hand hygiene compliance among health care workers in intensive care units

Abstract: Introduction: Studies indicate that adherence to hand hygiene guidelines is at suboptimal levels. We aimed to explore the reasons for poor hand hygiene compliance. Methodology: A qualitative study based on the Theory of Planned Behavior as a framework in explaining compliance, consisting four focus group discussions and six in-depth interviews. Results: Participants mostly practiced hand hygiene depending on the sense of "dirtiness" and "cleanliness". Some of the participants indicated that on-job training del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
2
8
0
4
Order By: Relevance
“…To explore the reasons for poor HH compliance we need to understand the beliefs and attitudes that shape HH behavior in our cultural setting [14,15]. A qualitative research has been planned and finalized to address these questions [16].…”
Section: Resultsmentioning
confidence: 99%
“…To explore the reasons for poor HH compliance we need to understand the beliefs and attitudes that shape HH behavior in our cultural setting [14,15]. A qualitative research has been planned and finalized to address these questions [16].…”
Section: Resultsmentioning
confidence: 99%
“…Mo et al (2019) found that women engaged in compensated dating had a higher intention for future HIV testing when their peers were supportive of the behavior. Ay et al (2019) showed that the subjective norm of healthcare workers towards hand hygiene was influenced by social cohesiveness and a sense of belongingness with the Intensive Care Unit team. White et al (2015) found that Australian nurses reported that their colleagues influenced their normative beliefs towards hand hygiene the most.…”
Section: Subjective Norm and Adherence To Quarantine Protocolsmentioning
confidence: 99%
“…Qualitative research methods can be very helpful because they examine individuals' beliefs, attitudes, experiences and intentions [27]. Based on the review of literature, no qualitative study investigated this issue, so we decided to analyze the experiences and views of healthcare workers qualitatively and discover the barriers to hand hygiene practice in the southeastern Iran.…”
Section: Introductionmentioning
confidence: 99%